2002
DOI: 10.1034/j.1600-0420.2002.800505.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age and colour content in fundus images

Abstract: ABSTRACT.Introduction: The morphological appearance of the ocular fundus is one of the key parameters used in the diagnosis and management of retinal disease. However, optical imperfections in the refractive media result in blurring, low luminance and contrast, and changes in the colour composition of the image which can be seen as an increasing yellowish appearance with age. The introduction of a method for quantifying this age-related change in colour content may help in diagnosing and grading pathological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Our attention maps highlighted the eye fundus vascular features, which are consistent with Poplin et al’s attention maps (Poplin et al, n.d.). Ege et al reported that with age, eye fundus images tend to become more yellow because of optimal imperfections in the refractive media (Ege et al, 2002), which was possibly leveraged by our neural networks and could explain why some non-vascularized regions were also highlighted. Finally, our attention maps highlighted most retinal layers in the OCT images.…”
Section: Discussionmentioning
confidence: 83%
“…Our attention maps highlighted the eye fundus vascular features, which are consistent with Poplin et al’s attention maps (Poplin et al, n.d.). Ege et al reported that with age, eye fundus images tend to become more yellow because of optimal imperfections in the refractive media (Ege et al, 2002), which was possibly leveraged by our neural networks and could explain why some non-vascularized regions were also highlighted. Finally, our attention maps highlighted most retinal layers in the OCT images.…”
Section: Discussionmentioning
confidence: 83%
“… 22 In addition, various structural abnormalities involving the optic disc were found associated with elongated AL, including PPA, 23 tilted disc, and enlarged optic disc crescent. 24 , 25 On the other hand, aging could affect the appearance of the fundus captured by CFP with multiple means, which include influencing the color presented in the photos, altering the retinal microvasculature, increasing the visibility of large choroidal vessels due to tessellation, 11 , 26 and even causing age-related macular degeneration. 27 In addition to AL and age, Korot et al 8 demonstrated that CFP could be used to predict sex via deep learning models, suggesting the presence of sex-related differences in the appearance of the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the color content of fundus images was found to be shifted during aging. 11 Remarkably, both retinal vascular structures and color content are included in CFP. Due to the age-related changes of CFP, Wang et al 12 developed convolutional neural network (CNN) models by integrating retinal fundus and vessel images as combined data inputs for predicting age, and the results showed commendable performance.…”
Section: Introductionmentioning
confidence: 99%
“…The retinal microvasculature shares similar anatomical and physiological features with other end organs including the brain, heart and kidneys, and subtle variations in retinal microvascular parameters (RMPs) may reflect similar variation within the cerebral, renal and coronary circulation [12][13][14]. Recent advances in retinal fundus imaging provide a unique and non-invasive assessment of the microvasculature currently not possible elsewhere in the body [15][16][17][18], enabling opportunistic evaluation of vascular disease and the wider systemic circulation [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%